Where the extraordinaries meet: a cascade of isosymmetrical superionic phase transitions and negative thermal expansion in a novel silver salt-inclusion borate halide. Issue 23 (30th May 2022) - Volkov, Sergey N.; Charkin, Dmitri O.; Arsentev, Maxim Yu.; Aksenov, Sergey M.; Manelis, Lev S.; Krzhizhanovskaya, Maria G.; Sinelshchikova, Olga Yu.; Ugolkov, Valery L.; Povolotskiy, Alexey V.; Shilovskikh, Vladimir V.; Antonov, Andrey A.; Bubnova, Rimma S.
Abstract : A new silver iodide borate, Ag3 B6 O10 I, is presented as a promising solid-state electrolyte with a δ ↔ γ ↔ β ↔ α cascade of the isosymmetric superionic phase transitions. Abstract : A new silver iodide borate, Ag3 B6 O10 I, is presented as a promising solid-state electrolyte with a δ ↔ γ ↔ β ↔ α cascade of the isosymmetric superionic phase transitions. Its crystal structure is composed of two sublattices, the "host" B–O covalent part from B6 O13 6B:3Δ3□:[φ]<Δ2□>|<Δ2□>|<Δ2□>| corner-sharing hexaborate groups, and the "guest" Ag–I ionic part. The transitions are associated with structural re-arrangements of the latter with a stepwise "melting" of silver sublattice and give rise to an increase in conductivity to 0.005 S cm −1 at 99 °C. Exceptionally large room-temperature anharmonicity of silver vibration has been described. The migration of silver ions leads to negative thermal expansion (NTE) at 25–400 °C. The sodium analog, Na3 B6 O10 I, with a "normal" perovskite-like structure was obtained. The structural diversity in the M3 B6 O10 X family can be rationalized considering the difference in the ionic radii of X − anions and M + cations.